THE INFLUENCE OF HEALTH EDUCATION WITH AUDIO VISUALS ABOUTANEMIA ON THE LEVEL OF KNOWLEDGE OF PREGNANT WOMENAT TOROH 1 HEALTH CENTER - Rindi; Sri Martini; Wahyu Dewi Hapsari (LPPM AN NUUR, 2024)
Background ; One of the biggest causes of Maternal Mortality Rate (MMR) is bleeding and one of the causes of bleeding is anemia which is also an indirect cause of maternal death, especially in pregnancy. The World Health Organization in Worldwide Prevalence of Anemia in 2022 shows that the prevalence of anemia in the world ranges from 40-88%. According to the 2021 Basic Health Research in Indonesia, the incidence of anemia in pregnant women in 2022 increased from 37.1% to 48.9%. Insufficient knowledge about anemia can result in less than optimal health behavior for pregnant women to prevent anemia in pregnancy. Objective ; The general aim of this research is to analyze the effect of audio-visual health education about anemia on the knowledge of pregnant women. Methodology ; This research is a quantitative research using a pre-experimental design with a one group pre test post test design. This type of non-probability sampling technique results in a sample of 30 respondents. Results ; Based on SPSS using the Wilcoxon test with a p-value of 0.000. If alpha (α) is <0.05. Conclusion ; Based on the research, there is an influence of health education with audio visuals about anemia on the level of knowledge of pregnant women at the Toroh 1 Community Health Center